2008
DOI: 10.5271/sjweh.1287
|View full text |Cite
|
Sign up to set email alerts
|

Does evening work predict sickness absence among female carers of the elderly?

Abstract: Objectives The aim of the present study was to predict the risk ratio of sickness absence lasting ≥2 weeks due to shift work among Danish workers caring for the elderly during the evening and at night. Methods A sample of Danish carers of the elderly were interviewed in 2005. The response rate was 78%. A cohort of 5627 shift and day workers was followed for sickness absence lasting ≥2 weeks and for sickness absence lasting ≥8 weeks in a sickness compensation register covering all social transfer payments in De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 25 publications
5
37
0
2
Order By: Relevance
“…Although not all studies have linked shift and night work with increased sickness absence (34,35), the vast majority of studies have shown that shift work is a risk factor for sickness absence (36)(37)(38)(39)(40). Seen strictly from a health perspective, night work should therefore be avoided.…”
Section: Resultsmentioning
confidence: 99%
“…Although not all studies have linked shift and night work with increased sickness absence (34,35), the vast majority of studies have shown that shift work is a risk factor for sickness absence (36)(37)(38)(39)(40). Seen strictly from a health perspective, night work should therefore be avoided.…”
Section: Resultsmentioning
confidence: 99%
“…Sykepleierne rapporterer også at forbedring av skiftordningene kan vaere en viktig metode for å få ned sykefravaeret for yrkesgruppen (13). En studie fra Island (14) viste ingen forskjeller i sykefravaer blant sykepleiere som jobbet turnus eller dagskift, mens man i en dansk studie (15) vaer med varighet over to uker sammenliknet med kontrollgruppe i fast dagskift. Alt i alt er det få studier som tar for seg relasjonen mellom sykefravaer og forskjellige skiftordninger i helsesektoren, og konklusjonene er inkonsistente (16).…”
Section: Bakgrunnunclassified
“…Dette samsvarer med funnene i en dansk studie som har funnet økt sykefravaer blant kvinnelige helsearbeidere i eldreomsorgen som arbeider kveldsskift (15). Den danske studien er imidlertid ikke helt sammenliknbar med vår, da de her sammenliknet dagarbeidere og ettermiddagsskiftarbeidere.…”
Section: Diskusjonunclassified
“…In a review study, Saksvik et al (2011) showed that adaptation to shift work was related to characteristics of the individual; for example, young age, male gender, high scores for flexibility and extraversion were association with higher shift work tolerance [14]. Prospective cohort and cross-sectional studies have shown that shift work is also associated with sickness absence and work ability [12,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The research results on the links between different shift work schedules and sickness absences ranging from strong connection [12,15,[18][19][20] and or no links [16,17]. In addition, previous studies have focused more on health care workers [16][17][21][22] to the relative neglect of the industrial sector [ 8,18].…”
Section: Introductionmentioning
confidence: 99%